2014
DOI: 10.1111/josl.12104
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary dynamics of postcolonial Englishes: A Hong Kong case study

Abstract: Schneider's (2007) ground-breaking Dynamic Model is widely regarded as the most comprehensive and coherent theory to account for the evolution of postcolonial Englishes, but has yet to be validated by evidence from detailed historical research. This article seeks to bridge this gap by presenting an empirically-grounded case study of the evolution of Hong Kong English based on the four parameters in Schneider's (2007) framework, viz. sociopolitical background, identity constructions, sociolinguistic conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Nonetheless, studies, even those that attempt to present HKE as variable and dynamic (cf. Evans ), ostensibly favor the former approach. That is, studies tend to attribute linguistic features to regions (e.g.…”
Section: The Single Linguistic Narrative: Hong Kongmentioning
confidence: 99%
“…Nonetheless, studies, even those that attempt to present HKE as variable and dynamic (cf. Evans ), ostensibly favor the former approach. That is, studies tend to attribute linguistic features to regions (e.g.…”
Section: The Single Linguistic Narrative: Hong Kongmentioning
confidence: 99%
“…Examples included "<…>when you"re doing say an interview^^ then maybe it"s less acceptable," mirroring the findings of Evans (2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last decade or so the debate has changed with several authors pointing towards recognisable and persistent features of HKE, such as in phonology, lexis and syntax, and its increasing overt use locally, especially Bolton (2002) who has championed the cause for HKE stating that it may already poses many of the required features of a NVE. Evans"s (2014) research showed the widespread use of English in the workplace due to its perceived links to professionalism and important works by Groves (2009;2011) (Groves, 2009). However, governmental, educational and business preference for native forms of English (Luk and Lin, 2006) To answer the above RQs, a mixed method approach was chosen because it was felt that such an approach would provide a breadth and depth of qualitative data that a single method could lack, whilst mitigating some of the possible disadvantages of each method respectively, (Patton 2002;Ivankova and Crewel 2009: pp.…”
Section: Introductionmentioning
confidence: 99%
“…The global spread of the English language, its multifarious uses, and its international role constitute highly complex processes that call for such descriptions and have actually given rise to explanations that categorize (or ‘catalogue’ in McArthur's terms) the plurality of Englishes in the world. Such categorization, however, comes at a price of generalization as Evans () highlights in a study on Hong Kong English:
The outcome of their kscientists] endeavours – a model or theoretical framework – does not, of course, correspond to messy, multifarious reality, but instead is an intentionally simplified or idealised conception of the essential features of a significant process, system or situation in their particular branch of science. (Evans : 572)
…”
Section: Introductionmentioning
confidence: 99%
“…Such categorization, however, comes at a price of generalization as Evans () highlights in a study on Hong Kong English:
The outcome of their kscientists] endeavours – a model or theoretical framework – does not, of course, correspond to messy, multifarious reality, but instead is an intentionally simplified or idealised conception of the essential features of a significant process, system or situation in their particular branch of science. (Evans : 572)
…”
Section: Introductionmentioning
confidence: 99%